THESIS SIMILARITY DETECTION APPLICATION AT BANTEN JAYA UNIVERSITY - Raden Kania; Tifani Intan Solihati; Fakhri Noor Arzaqi (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
The ease of accessing information results in an increase in the level of plagiarism. Plagiarism is an act of tacking other peoples’ writings or opinions and making it look as if they were by themselves without first studying and not including the source. A detection similarity is an application that is made based on a website to detect the similarity or similarity of a document/text with other documents/text. In addition, il also provides an overview of the calculation sequence of how the calculation process in detecting the text runs until it produces the percentage of similarity of the text. In a making-based application website, this methodology used is the waterfall. While the method used in calculating the similarity of the text is the Algorithm Winnowing. The winnowing algorithm is one of the document method fingerprints. This method can identify the similarity of the test, including small parts that are similar in a set of documents that are analyzed through the fingerprint generated and for calculating the percentage results using the Jaccard Coefficient. The Smaller the percentage level of similarity of a text document, the smaller the level of similarity, but if the percentage value is greater then can be ascertained that the document is plagiarized. The winnowing algorithm can be used as a plagiarism check in thesis and journal documents. The application built in this system is running well because the winnowing algorithm can help check plagiarism in the thesis and journal documents.